Synthesis and evaluation of smart drugs with integrated functions for identifying and treating oxidative microenvironments associated with cellular ferroptosis - Yibo Zhang; Rui Cai; Yu Ding; Jiangye Zhang; Changxu Ning; Jiangcheng Zeng; Zhongxiang Zhou; Shisheng Wang; Yueqing Li; Xiuhan Guo (Smart Molecules)
Abstract Ferroptosis is a novel form of cell death driven by oxidative damage, and is implicated in various pathological conditions, including neurodegenerative diseases, retinal damage, and ischemia‐reperfusion injury of organs. Inhibiting ferroptosis has shown great promise as a therapeutic strategy for these diseases, underscoring the urgent need to develop effective ferroptosis inhibitors. Although Ferrostatin‐1 (Fer‐1) is a potent ferroptosis inhibitor, its susceptibility to oxidation and metabolic inactivation limits its clinical utility. In this study, the accumulation of peroxides and the resulting oxidative damage in the cellular microenvironment during ferroptosis were utilized to design Ferrostatin‐1 prodrugs with reactive oxygen species‐responsive features. This approach led to the development of a series of ferroptosis inhibitors that were capable of recognizing oxidative damage in diseased areas, allowing for targeted release and improved stability. The novel compounds demonstrated significant inhibitory effects and selectivity against RSL‐3‐induced ferroptosis in HK‐2 cells, with compound a1 exhibiting an EC50 of 15.4 ± 0.7 μM, outperforming Fer‐1. These compounds effectively identify the oxidative microenvironment associated with ferroptosis, enabling the targeted release of Fer‐1, which prevents lipid peroxide accumulation and inhibits ferroptosis. This strategy holds promise for treating diseases related to ferroptosis, offering a targeted and intelligent therapeutic approach.